Korean dual-career judokas` junior-to-senior transition: a longitudinal study - Hong, H. J.; Hong, S. H. (The Sport Psychologist, 2024)
This study adopts the athletic career transition model to explore the experiences of Korean dual-career (DC) judokas during their junior-to-senior transition using a longitudinal approach. We recruited 12 Korean elite judokas, all of whom were in their first year of university during their initial interview. Participants were organized into three focus groups, with three rounds of interviews conducted over approximately 2 years, totaling nine focus-group sessions. Thematic analysis was applied, which led to the identification of three key themes: (a) multifaceted challenges, (b) coping strategies, and (c) perceived needs of DC athletes prioritizing sport over study. The results indicate that Korean DC judokas share some common challenges (e.g., increased training demands, balancing their studies with training demands) with their European counterparts, but they also face unique challenges (e.g., managing weight control, laundry duties, and relationships with senior judokas) specific to the Korean judokas. Their coping strategies include both internal resources (e.g., focusing on performance target, utilizing resilience) and external ones (e.g., seeking social support), emphasizing the critical role of psychological support during their junior-to-senior transition. Proactive psychological support is recommended through a specialized system tailored to this group. Given that Korean DC judokas significantly prioritize sport over education, this system should also address balancing both sport and education.